Studi Pengaruh Lama Penumpukan Batubara terhadap Kualitas Proximate Batubara di ROM Coal Stockpile pada PT Multi Harapan Utama Kabupaten Kutai Kartanegara Provinsi Kalimantan Timur - Ronal Ronal; Windhu Nugroho; Revia Oktaviani; Agus Winarno; Ardhan Ismail (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
During the coal stockpiling process, the quality of coal may increase or decrease due to direct exposure to open environmental conditions, which can lead to changes in its characteristics. The longer the coal is stored in an open area, the more it undergoes changes caused by rainfall, heat, and air exposure, resulting in an increase in moisture content and ash content, while the calorific value decreases. Therefore, this research was conducted to determine the optimal coal stockpiling duration at the ROM coal stockpile to ensure that the calorific value does not significantly decrease. Coal sampling was carried out every two days from the initial time of stockpiling. After a two-month stockpiling period, the final coal quality results showed a total moisture of 13.89% (ar), inherent moisture of 15.95% (ad), ash content of 4.59% (ad), volatile matter of 40.3% (ad), and fixed carbon of 39.16% (ad). Based on these results, it can be concluded that the recommended storage duration for MCV-HS type coal at the ROM coal stockpile is 154 days. The laboratory analysis results obtained during the research indicate that the longer the coal is stored, the higher the moisture content and ash content become, while the calorific value continues to decrease. This occurs due to water absorption and oxidation reactions that take place during the coal storage period in the ROM coal stockpile.